MODAL SOSIAL PENGELOLA DALAM PENGEMBANGAN WISATA ALAM PUNCAK ULU KASOK DI DESA PULAU GADANG KECAMATAN XIII KOTO KAMPAR, KABUPATEN KAMPAR) - Randa Septian; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
This study discusses the use of social capital in the development of Puncak Ulu Kasok Tourism Object. This tourism development aims to provide benefits and benefits for the surrounding community, besides that tourism development must be in accordance with careful planning so that it is beneficial to the community, both in terms of economy, social and culture. This study aims to determine: How is the social capital of the community in the development of ulu kasok tourism in Pulau Gadang Village. This study uses qualitative methods, the data sources used are primary data and secondary data. Research informants who became key informants in this study were 5 people, namely: 4 Ulu Kasok tourism managers also an owner of Ulu Kasok tourism. Data collection techniques using interviews, observation and documentation. The results obtained in this study in managing and developing Puncak Ulu Kasok Tourism, it has been influenced by social capital. In this case, they really use social capital to manage and develop tourism by establishing a network. In order to strengthen trust then build a network with norms. The norms they used are unwritten norms. Keywords: Tourism Development, Organizer, Social Capital